Safety of tracheal intubation in the presence of cardiac disease in paediatric ICUs. (25th April 2018) - Gradidge, Eleanor A.; Bakar, Adnan; Tellez, David; Ruppe, Michael; Tallent, Sarah; Bird, Geoffrey; Lavin, Natasha; Lee, Anthony; Nadkarni, Vinay; Adu-Darko, Michelle; Bain, Jesse; Biagas, Katherine; et al.
Abstract: Introduction: Children with CHD and acquired heart disease have unique, high-risk physiology. They may have a higher risk of adverse tracheal-intubation-associated events, as compared with children with non-cardiac disease. Materials and methods: We sought to evaluate the occurrence of adverse tracheal-intubation-associated events in children with cardiac disease compared to children with non-cardiac disease. A retrospective analysis of tracheal intubations from 38 international paediatric ICUs was performed using the National Emergency Airway Registry for Children (NEAR4KIDS) quality improvement registry. The primary outcome was the occurrence of any tracheal-intubation-associated event. Secondary outcomes included the occurrence of severe tracheal-intubation-associated events, multiple intubation attempts, and oxygen desaturation. Results: A total of 8851 intubations were reported between July, 2012 and March, 2016. Cardiac patients were younger, more likely to have haemodynamic instability, and less likely to have respiratory failure as an indication. The overall frequency of tracheal-intubation-associated events was not different (cardiac: 17% versus non-cardiac: 16%, p=0.13), nor was the rate of severe tracheal-intubation-associated events (cardiac: 7% versus non-cardiac: 6%, p=0.11). Tracheal-intubation-associated cardiac arrest occurred more often in cardiac patients (2.80 versus 1.28%; p<0.001), even after adjusting for patient and provider differences (adjusted odds ratio 1.79; p=0.03). Multiple intubation attempts occurred less often in cardiac patients (p=0.04), and oxygen desaturations occurred more often, even after excluding patients with cyanotic heart disease. Conclusions: The overall incidence of adverse tracheal-intubation-associated events in cardiac patients was not different from that in non-cardiac patients. However, the presence of a cardiac diagnosis was associated with a higher occurrence of both tracheal-intubation-associated cardiac arrest and oxygen desaturation.